The Difference of Eosinophil Amount in Tuberculosis Patients with and without Soil-Transmitted Helminths Co-infection in Panti District, Jember - Yunita Armiyanti; Nisrina Salsabila Firmansyah; Angga Mardro Raharjo; Muhammad Ali Shodikin; Enny Suswati; Dini Agustina (Faculty of Nursing, Universitas Jember, 2020)
Tuberculosis is one of the world's health problems even in Indonesia. The immune response that needed to deal with TB can be influenced by other infections, such as helminth infection. The helminth infections induce Th2 immune responses and eosinophilia to eliminate these pathogen. Meanwhile, the Th2 response and eosinophilia can also suppress the Th1 immune response which is very important to eliminate the bacterium M. tuberculosis and make a negative impact on the success of TB therapy. Thus, the eosinophil profile can describe the immune response in TB patients with helminth co-infection. This study aims to determine the prevalence of helminthiasis in TB patients and determine the differences in eosinophil amount in tuberculosis patients with and without helminth co-infection. This study was an observational analytic study with a cross-sectional design conducted at Puskesmas Panti in August 2019-January 2020 using fecal and blood samples from 24 research subjects. Helminth co-infection status was obtained from fecal examination with sedimentation and flotation methods while the number of eosinophils was obtained from leukocyte counts. Data analysis used the Mann Whitney U test to determine differences in the number of eosinophils in the two groups. The results showed there was no difference in the number of eosinophils in TB patients with helminth co-infection and without helminth co-infection (p> 0.05). There is no typical picture of the number of eosinophils in both groups so that eosinophils cannot describe the immune response that arose in TB patients with helminth co-infections in Panti district, Jember.